Papel do receptor aril-hidrocarbono (AhR) na malária cerebral experimental causada por Plasmodium berguei Anka - Fatima Maria Caldeira Brant Costa (2011)
The cerebral malaria (CM) is the major complication found in the individuals infected by the P. falciparum. However, the events that result in the development of CM are multi-factorial and could not be explained for only one mechanism. Mice infected with P. berghei ANKA (PbA) faithfully recapitulate many of the characteristics of human CM and it has been an important tool to investigate the disease pathogenesis. The Aryl Hydrocardon receptor (AhR) is an intracellular receptor activated by ligands and is important to modulate the inflammatory response. However, the involvement of AhR in CM is not known. The parasitemia was dramatically higher in AhRKO infected with PbA. In the spleen of PbA-infected AhRKO mice there was a significant increased expression INF, IL-12, IL-10 and decrease expression of TNF- e TGF- when compared with infected WT mice. Additionally, there was an increased level of TGF-, IL-6, IL-17 and high expression of FOXP3 in the brain of infected AhRKO mice when compared with WT counterparts. This date seems possible maybe indicated that Th17 polarization is promoted by stimulation of the AhR a ligand-dependent. Our results show an increase levels of hepatic transaminases, especially ALT, increased inflammation and degeneration, as well as increase iron concentration in serum during infection in mice AhRKO PbA. All these changes may indicate that severe injury occurred in the liver of animals infected with AhRKO PbA. AhR-deficient mice infected, had an increase in permeability of the BBB, which together with the inflammatory and metabolic changes may have contributed to the development of pathology in these animals culminating in early death observed. Our data suggest that AhR may contribute significantly to the development of CM.